2012
DOI: 10.1186/1479-5876-10-97
|View full text |Cite
|
Sign up to set email alerts
|

The CRKL gene encoding an adaptor protein is amplified, overexpressed, and a possible therapeutic target in gastric cancer

Abstract: BackgroundGenomic DNA amplification is a genetic factor involved in cancer, and some oncogenes, such as ERBB2, are highly amplified in gastric cancer. We searched for the possible amplification of other genes in gastric cancer.Methods and ResultsA genome-wide single nucleotide polymorphism microarray analysis was performed using three cell lines of differentiated gastric cancers, and 22 genes (including ERBB2) in five highly amplified chromosome regions (with a copy number of more than 6) were identified. Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 34 publications
2
28
0
Order By: Relevance
“…Some oncogenes are highly amplified in GC. CRKL shows an important role in GC development with potential utilization as a molecular therapy target [18] CRKL amplification was found consistent with CRKL overexpression in GC. An extremely high CRKL copy number was detected in MKN74 GC cell line using fluorescence in situ hybridization, which was consistent with a high level of CRKL expression determined by western blotting assay.…”
supporting
confidence: 54%
See 2 more Smart Citations
“…Some oncogenes are highly amplified in GC. CRKL shows an important role in GC development with potential utilization as a molecular therapy target [18] CRKL amplification was found consistent with CRKL overexpression in GC. An extremely high CRKL copy number was detected in MKN74 GC cell line using fluorescence in situ hybridization, which was consistent with a high level of CRKL expression determined by western blotting assay.…”
supporting
confidence: 54%
“…IHC analysis revealed that CRKL was overexpressed in primary GC tissues. Concordantly, CRKL amplification by determining CRKL copy number using fluorescence in situ hybridization was positively correlated with its overexpression in primary GC tissues [18]. Finally, MKN74 cells with CRKL amplification were responsive to dual Src/BCR-ABL kinase inhibitor BMS354825, likely via the inhibition of CRKL phosphorylation, indicating CRKL may be a target of BMS354825-mediated therapy for a subset of GC.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…The areas evaluated were a small core of the TMA (2 mm in diameter) and the apparent intratumor heterogeneity was negligible. (24)(25)(26) Western blotting was performed as described previously. (22) btubulin (1:1000) was used as an internal control.…”
Section: Methodsmentioning
confidence: 99%
“…CRKL commonly localizes in multiple intracellular compartments mapped at 22q11.21 encoding a protein of 36 kDa [14]. CRKL deregulation is involved in the development and progression of a variety of cancers including gastric cancer (GC), glioblastoma multiforme (GBM), hepatocellular carcinoma (HCC), bladder cancer, lung cancer, colon cancer, ovarian cancer, leukemia, breast cancer, head and neck cancer, rhabdomyosarcoma and neuroblastoma [15][16][17][18][19][20][21][22]. Nevertheless, the role and action mechanism of CRKL in tumor progression are still unclear.…”
Section: Introductionmentioning
confidence: 99%